A S-doped high-K oxide dielectric film and its preparation method and application
By doping sulfur in the high K oxide dielectric film and using sulfuric acid as the S source, an S-doped high K oxide dielectric film was prepared, which solved the problem of many defect states in the existing technology, and achieved better dielectric performance and performance stability.
Patent Information
- Application Number
- CN202211281620.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-10-19
AI Technical Summary
The existing solution method has many defect states for preparing high K oxide dielectric films, which leads to high leakage current and serious capacitance-frequency dependence characteristics of the dielectric film.
S-doped high K oxide dielectric films are prepared by doping sulfur (S) into the high K oxide dielectric film and using sulfuric acid as the S source. The method includes dissolving nitrate in water, adding aqueous sulfuric acid solution to produce a precursor solution, coating it on the substrate and performing pre-annealing and final annealing treatment.
S-doping can improve the dielectric properties of high-K oxide dielectric films, reduce defect states, reduce leakage current, suppress capacitor-frequency dependence characteristics, and improve the density and performance stability of the film.
Smart Images

Figure CN115513062B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thin film transistor devices, and in particular to an S-doped high-K oxide dielectric film and a preparation method and application thereof. Background Art
[0002] With the development of practical application requirements such as large-scale integrated display, flexible display, transparent display, wearable display, etc., thin-film transistor (TFT), as one of the active driving elements, plays a very important role in panel display, and therefore has been widely studied in recent years. In the development process of TFT, silicon-based TFT, organic TFT and oxide TFT have emerged. Among them, the rise of oxide TFT originated from the invention of a-IGZO TFT, which has many advantages such as high mobility, good electrical properties, and can be applied to flexible and transparent displays.
[0003] The preparation methods of oxide TFTs can be generally divided into two types: vacuum method and solution method. Although the performance and stability of TFT devices prepared by the solution method are currently poor, it cannot be ignored that the solution method has outstanding advantages in terms of low cost and high efficiency. However, although the solution method for preparing high-K oxide dielectric layers is fast and simple, it is not easy to prepare dense and flat films. The solution method preparation of dielectric layer films usually requires high-temperature annealing to form a dense oxide framework. However, this high-temperature annealing often exceeds the tolerance temperature of most soft matrix substrates, making the high-K oxide dielectric films prepared by the solution method contain more defect states, resulting in a higher leakage current of the dielectric film and a more serious capacitance-frequency dependence. Therefore, the development of the solution method preparation of high-K gate dielectric materials in the field of flexible wearable displays is limited.
[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide an S-doped high-K oxide dielectric film and a preparation method and application thereof, aiming to solve the problem that the existing solution method for preparing high-K oxide dielectric films contains more defect states, resulting in a higher leakage current of the dielectric film.
[0006] The technical solution of the present invention is as follows:
[0007] A method for preparing an S-doped high-K oxide dielectric film comprises the following steps:
[0008] Dissolving nitrate in water and stirring to obtain a nitrate solution; adding a sulfuric acid aqueous solution to the nitrate solution to obtain a precursor solution;
[0009] Providing a substrate, and cleaning, drying, and plasma treating the substrate;
[0010] The precursor solution is coated on the surface of the substrate after plasma treatment, and a pre-annealing treatment is performed; finally, a final annealing treatment is performed to obtain an S-doped high-K oxide dielectric film.
[0011] An S-doped high-K oxide dielectric film is prepared by using the preparation method of the S-doped high-K oxide dielectric film.
[0012] An application of the S-doped high-K oxide dielectric film, wherein the S-doped high-K oxide dielectric film is used as a dielectric layer of a thin film transistor.
[0013] Beneficial effects: The present invention provides an S-doped high-K oxide dielectric film and a preparation method and application thereof. The preparation method can improve the increase amplitude of low-frequency capacitance of the high-K oxide dielectric film under bias by S doping, suppress the capacitance frequency dependence characteristics, and reduce the free H in the film. + content, which improves the performance stability of the corresponding TFT device; at the same time, it can improve the dielectric properties of the dielectric film prepared by the solution method, making the film denser and reducing the defect state, which is equivalent to increasing the annealing temperature. In addition, S exists in the film in the form of sulfate. In the configured solution, SO4 2- It can replace water ligands and has a high complexing ability with adjacent metal ions to form complexes; in the post-annealing process, SO4 2- It can be retained in thermal annealing and act as a network former to make the oxide skeleton denser. S doping into high-K oxide dielectric films can fill oxygen vacancies in the film and eliminate a large number of hydroxyl groups to connect the metal oxygen skeleton, which makes the film denser and reduces the amount of free hydrogen ions that can be generated, thus avoiding the generation of additional capacitance. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 In2O3 / AlSO in Example 1 of the present invention X Schematic diagram of TFT device preparation;
[0015] Figure 2 (a) shows AlSO with different S doping amounts. X GIXRD patterns of the films, (b) AlSO with different S doping amounts X AFM images of the films, (c) AlSO with different S doping amounts X Refractive index diagram of the film, (d) AlSO with different S doping amounts X FTIR spectra of precursor powders, (e) AlSO with different S doping amounts XLight transmittance diagram of the film, (f) is AlSO with different S doping amounts X Light absorption coefficient spectrum of thin films;
[0016] Figure 3 (a) is AlSO doped with 0 at% S X Thermogravimetric-derivative thermogravimetric analysis of the dried powder of the precursor solution, (b) AlSO doped with 8at% S X Thermogravimetric-derivative thermogravimetric analysis of the dried powder of the precursor solution;
[0017] Figure 4 (a) shows AlSO with different S doping amounts. X O1s spectra and peak fitting results of the films, (b) AlSO with different S doping amounts X The O1s fitting peak area ratio of the film, (c) is AlSO with different S doping amounts X Al 2p core level spectrum of the film, (d) AlSO with different S doping amounts X S2p core level spectrum of the film, (e) AlSO with different S doping amounts X S / [S+Al] atomic ratio relationship diagram of the film;
[0018] Figure 5 (a) shows AlSO with S doping of 0at% and 8at%. X 3D-TOF-SIMS characterization of the H content of the film, (b) AlSO with S doping of 0at% and 8at% X 3D-TOF-SIMS characterization of the Al content of the film, (c) AlSO with S doping of 0at% and 8at% X 3D-TOF-SIMS characterization of the S content of the film, (d) 0at% S AlSO X 3D rendering of the distribution of H, Al, and S in the film, (e) 8at% S AlSO X 3D rendering of the distribution of H, Al, and S in the film;
[0019] Figure 6 (a) is 0at% S AlSO X thin film 27 AlNMR spectrum, (b) 8at% S AlSO X thin film 27 AlNMR spectrum, (c) 16at% S AlSO X thin film 27 AlNMR spectra, (d) for each film 27 The proportion of Al(O)4, Al(O)5 and Al(O)6 ligands in AlNMR spectra;
[0020] Figure 7 (a) is AlSO before doping X Schematic diagram of metal network, (b) AlSO after doping X Schematic diagram of metal network;
[0021] Figure 8 AlSO with different S doping amounts X The data of the film at 0V, 1V and 2V bias voltages, where (a) is the frequency-capacitance characteristic curve, (b) is the S-doping amount-capacitance diagram at the relevant frequency, and (c) is the S-doping amount-dielectric constant diagram at the relevant frequency;
[0022] Fig. 9 AlSO with different S content X Analysis diagram of leakage current characteristics of the film, where (a) is the leakage current characteristic diagram; (b) is the leakage current characteristic diagram of 20 AlSO X (c) is the leakage current conduction diagram under low electric field strength (ln(J / E) vs.E 1 / 2 (PF emission)); (d) leakage current conduction diagram under high electric field strength (ln(J / T 2 )vs.E 1 / 2 (SE emission));
[0023] Fig.10 (a) is In2O3 / AlSO X (8at%S) TFT device structure diagram; (b) In2O3 / AlSO X (8at%S) / P++-Si cross-sectional TEM image; (c) is the HR-TEM image of ln2O3 film; (d) is the FFT pattern of ln2O3 film; (e) is the AlSO X EDS spectrum of (8at%S) film and corresponding element scanning distribution diagram;
[0024] Fig.11 (a) shows In2O3 / AlSO with different doping concentrations X Transfer curves of TFT devices, (b) In2O3 / AlSO with different doping concentrations X Output curve of TFT device;
[0025] Fig.12 ln2O3 / AlSO with different S doping amounts X Transfer curves and threshold voltage-bias voltage time relationships of TFT devices, where (a), (b), and (c) are PBS, and (d), (e), and (f) are NBS;
[0026] Fig.13 The AlSO with 0 and 8 at% S doping at 250°C X Analysis of leakage current characteristics of the film, where (a) is the leakage current characteristic curve; (b) is the capacitance-frequency characteristic curve under 0V bias; (c) is the capacitance-frequency characteristic curve under 2V bias; (d) is ln2O3 / AlSO X Transfer curves of the device; (e) and (f) are ln2O3 / AlSO X Output curve graph of the device;
[0027] Fig.14 ZrSO with different S doping amounts X GIXRD patterns of thin films;
[0028] Fig.15 ZrSO with different S doping amounts X AFM images of thin films;
[0029] Fig.16 ZrSO at different doping concentrations X XPS spectra of the film and its peak fitting results, where (a) is the O1s spectrum and peak fitting results, (b) is the O1s fitting peak area ratio, (c) is the S2p core level spectrum, and (d) is the Zr 3d 5 / 2 and Zr3d 3 / 2 Core energy level spectrum; (e) is the S / [S+Zr] atomic ratio relationship diagram;
[0030] Fig.17 (a) shows ZrSO with different S doping amounts. X Bias capacitance characteristic curve of the film, (b) is ZrSO with different S doping amounts X Leakage current characteristic curve of the film;
[0031] Fig.18 (a) is based on In2O3 / ZrSO with different S doping amounts X Transfer curve of TFT device, (b) is In2O3 / ZrSO based on different S doping amounts X Output graph of TFT device;
[0032] Fig.19 MSO with S doping amounts of 0 and 10 at% X AFM images of dielectric films. DETAILED DESCRIPTION
[0033] The present invention provides an S-doped high-K oxide dielectric film and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0034] SiO2 is easily found in dust, sand, and minerals and is considered to be a very good insulator (resistivity of about 10 16 Ωcm), can be prepared into high-quality defect-free dielectric films. Therefore, the abundant SiO2 material enjoys a high status in today's complementary metal oxide semiconductor (CMOS) technology.
[0035] At present, with the increasing requirements for the degree of integration, minimizing the size of electronic components has become one of the core issues in the electronics field. Reducing the thickness of the SiO2 dielectric layer has also become a cutting-edge research hotspot, and it is becoming increasingly necessary to achieve smaller, faster, and cheaper electronic circuits. However, SiO2 has its physical size limit as a gate dielectric layer; when the thickness of the SiO2 layer is reduced to the atomic scale, it will cause direct tunneling of the SiO2 layer. Some researchers have analyzed through experiments and physical models that the minimum physical thickness of the SiO2 film that maintains a complete bandgap structure is 0.7nm. Even if it is close to this theoretical value, the leakage current density (J leak ) becomes too high. When the SiO2 film thickness is 1.2nm, the gate leakage current at 1V exceeds 1A / cm 2 , which can cause serious problems in standby power consumption and device reliability.
[0036] One of the solutions is to introduce high-K oxide dielectric materials to replace SiO2. High-K oxide dielectric materials can have a larger equivalent thickness while maintaining the same capacitance as the SiO2 dielectric layer, which can effectively suppress the sharp increase in leakage current under tunneling dimensions. In addition, the reduction in the lateral size of the transistor requires a larger unit area capacitance of the dielectric layer to maintain the gate's control over carriers in the channel layer. High-K oxide dielectric materials can solve these problems well, which makes it possible to further reduce the device feature size and further increase the integration. In addition. The operating voltage of TFT devices based on SiO2 dielectric films is generally -30 to 30V, while TFT devices based on high-K dielectric films can meet the operating voltage range of -5 to 5V, which further broadens the application range of its devices. In 2018, the ultra-thin HfO2 / IGZO TFT device studied by Pengfei Ma et al. achieved an ultra-low operating voltage of 1V.
[0037] At present, the developed high-K dielectric materials mainly include nitrides, metal oxides, etc. However, as the performance requirements of devices become higher and higher, people's attention is focused on high-K metal oxides. Among them, the most representative is HfO2 gate dielectric material, which has been applied to actual products. The selection criteria of high-K gate dielectric materials include suitable dielectric constant (>10), suitable band gap width (>5eV), good moisture absorption resistance, and good surface morphology and defect state.
[0038] However, the high-K oxide dielectric film prepared by the existing preparation method contains a large number of defect states, resulting in a high leakage current of the dielectric film and a relatively serious capacitance-frequency dependence characteristic.
[0039] Based on this, the present invention provides a method for preparing an S-doped high-K oxide dielectric film, comprising the steps of:
[0040] Step S10: dissolving nitrate in water and stirring to obtain a nitrate solution; adding a sulfuric acid aqueous solution to the nitrate solution to obtain a precursor solution;
[0041] Step S20: providing a substrate, and cleaning, drying, and plasma treating the substrate;
[0042] Step S30: coating the precursor solution on the surface of the plasma-treated substrate, and performing a pre-annealing treatment; and finally performing a final annealing treatment to obtain an S-doped high-K oxide dielectric film.
[0043] In this embodiment, a dielectric film is prepared by doping a high-K oxide with sulfuric acid as an S source, and as the S doping amount increases, its band gap gradually increases; defects in the film will produce localized states in the band gap, thereby resulting in a decrease in the band gap energy, and a large band gap also reflects high-quality film formation. Therefore, S doping can reduce defects formed by oxygen vacancies in the dielectric film.
[0044] Specifically, in the dielectric film prepared by S doping into high-K oxide, S plays two roles in the dielectric film: one is to fill the oxygen vacancies in the film; the other is to eliminate a large number of hydroxyl groups and connect the metal oxygen skeleton. This makes the film denser, and the content of free hydrogen ions that can be produced is also reduced; thus, the low-frequency capacitance of the dielectric film is more stable, that is, the capacitance-frequency dependence of the S-doped high-K oxide dielectric film is suppressed. At the same time, the dielectric properties of the S-doped high-K oxide dielectric film at low electric field strength are improved, mainly because there are no defects that can serve as carriers of leakage current. Therefore, S doping improves the leakage current performance of the dielectric film because the role of the leakage current mechanism in the film has changed to a certain extent.
[0045] In some embodiments, the nitrate is selected from but not limited to one of AlN3O9·9H2O, N2O7Zr·xH2O, Ga(NO3)3·xH2O, N3O9Sc·xH2O, N3O9Ho·xH2O, and N3O9Sm·6H2O. These nitrates are used to achieve the dielectric properties of the dielectric film obtained by S doping, and the capacitance-frequency dependence characteristics can be suppressed; in addition, S doping has a more obvious ability to suppress moisture absorption and dehydroxylation of lanthanide high-K oxide materials, and makes the low-frequency capacitance of this series of films under bias more stable, which has important guiding significance for lanthanide high-K oxide materials that are troubled by hygroscopicity. Therefore, the S doping method is universal, can improve the dielectric properties of high-K oxide dielectric materials prepared by solution method, and can suppress the capacitance-frequency dependence characteristics.
[0046] In some embodiments, the mass fraction of the sulfuric acid aqueous solution is greater than or equal to 70%, and the purity of the sulfuric acid aqueous solution is 98%; that is, the sulfuric acid aqueous solution is concentrated sulfuric acid. The S in the S-doped high-K oxide dielectric film exists in the film in the form of sulfate. In the configuration solution, SO4 2- It can replace water ligands and has a high complexing ability with adjacent metal ions to form complexes; in the post-annealing process, SO4 2- It can be retained in thermal annealing and act as a network former, making the oxide framework denser; among them, SO4 2- As oxygen-containing anions, they can provide additional oxygen to the film, which can also be reflected in the change of film thickness.
[0047] In some embodiments, in step S20, the steps of cleaning, drying, and plasma treating the substrate include: soaking the substrate in acetone, anhydrous ethanol, and ultrapure water in sequence and ultrasonically cleaning them for 8-12 minutes respectively; after cleaning, drying the substrate with nitrogen and placing it in a plasma cleaning machine, and plasma treating it in an oxygen atmosphere for 8-12 minutes. Soaking the substrate in acetone, anhydrous ethanol, and ultrapure water for ultrasound, drying it with nitrogen, and then plasma treating it in an oxygen atmosphere can enhance the surface hydrophilicity of the substrate, so that the precursor solution can be more evenly coated on the surface of the substrate.
[0048] Specifically, a 13×13 mm Si substrate was soaked in acetone, anhydrous ethanol, and ultrapure water and ultrasonically cleaned for 10 min in sequence; after cleaning, it was blown dry with nitrogen and placed in a plasma cleaning machine (model: Diener Plasma Atto) and treated with Plasma for 10 min in an appropriate oxygen atmosphere to increase the surface hydrophilicity of the substrate.
[0049] In this embodiment, the substrate is a P-type heavily doped low-resistance silicon (P++-Si).
[0050] In some embodiments, the coating method is spin coating; the rotation speed of the spin coating is 5000 rpm / s, and the spin coating time is 28 - 32 s.
[0051] Specifically, a syringe is used to suck the prepared precursor solution, the needle is removed, and a 0.2 μm injection filter head is installed on the syringe. Subsequently, the precursor solution is dropped onto the substrate placed on a spin coater (model Spin Master 51), and spin coating is performed at a speed of 5000 rpm / s for 30 s. After spin coating, pre-annealing treatment and final annealing treatment are carried out.
[0052] In some embodiments, the pre-annealing treatment is carried out at a temperature of 140 - 160 °C for 4 - 6 min to rapidly evaporate deionized water and form a thin film; the final annealing treatment is carried out at 250 - 400 °C for 0.8 - 1.2 h to remove hydroxyl groups and oxygen vacancy defects in the thin film. Preferably, the temperature of the final annealing treatment is 300 - 400 °C, and the annealing time is 1 h.
[0053] Specifically, after the precursor solution is coated on the surface of the substrate, the sample is immediately placed on a heating table at 150 °C for 4 - 6 min of pre-annealing treatment; then the temperature is raised to 350 °C, and a 1 h final annealing treatment is completed in an atmospheric atmosphere; at this temperature, since the contents of hydroxyl groups and nitrate ions in the thin film almost disappear, the device characteristics of the dielectric thin film are better.
[0054] In some embodiments, the concentration of the precursor solution is 1.0 - 2.0 mol / L; the molar percentage a of S element in the precursor solution in the total of S and metal ions is 0 < a ≤ 24 at%. At this concentration, since SO4 2- has a strong complexing ability with metal cations, it can reduce the defect states (hydroxyl groups, oxygen vacancies) in the thin film, making the device characteristics of the high-K oxide dielectric thin film with S doping better. Appropriate S doping can improve the dielectric properties of Al2O3 prepared by the solution method, change the conduction mechanism of its leakage current, thereby reducing the leakage current and increasing the breakdown electric field strength; because it has oxygen-rich groups incorporated into the Al2O3 thin film skeleton, more hydroxyl groups and vacancies are recombined, making the thin film denser and the defect states reduced. However, excessive S doping will cause deterioration of the dielectric properties; because the dehydroxylation and the degree of skeleton filling will reach saturation, excessive incorporation will instead become impurities that破坏 the original dense structure.
[0055] It should be noted that there is an unclear expression "破坏" in the original text. It might be a typo. You can check and correct it if necessary.In addition, the present invention also provides an S-doped high-K oxide dielectric film, which is prepared by the preparation method of the S-doped high-K oxide dielectric film. The S-doped high-K oxide dielectric film obtained by the preparation method combining the solution method and the S-doping method can effectively reduce the leakage current of the dielectric film and suppress the capacitance-frequency dependence characteristics.
[0056] At the same time, the present invention also provides an application of an S-doped high-K oxide dielectric film, wherein the S-doped high-K oxide dielectric film is used as a dielectric layer of a thin film transistor.
[0057] In some embodiments, the method for preparing the thin film transistor comprises the steps of:
[0058] Step S1: dissolving indium nitrate powder in water and stirring to obtain an In2O3 precursor solution;
[0059] Step S2: plasma cleaning the S-doped high-K oxide dielectric film and then blowing it clean with nitrogen; coating the In2O3 precursor solution on the surface of the S-doped high-K oxide dielectric film after blowing clean with nitrogen, and performing annealing to obtain an In2O3 active layer on one side of the S-doped high-K oxide dielectric film;
[0060] Step S3: evaporating two spaced-apart metal electrodes on a side of the In2O3 active layer away from the S-doped high-K oxide dielectric film to obtain the thin film transistor.
[0061] In some embodiments, the concentration of the In2O3 precursor solution is 0.13 mol / L; and the annealing treatment is annealing at a temperature of 350°C for 1 hour.
[0062] Specifically, after the In2O3 active layer is prepared, a mask plate is attached to the In2O3 active layer using a high temperature resistant polyimide tape, and an aluminum electrode of about 100 nm is deposited on the surface of the active layer using a thermal evaporation deposition method, and finally Al / In2O3 / MSO is prepared. X A bottom-gate top-contact TFT device of a P++-Si structure, wherein M is one of Al, Zr, Ga, Sc, Ho, and Sm. In addition, the length of the prepared electrode is 1500 μm, the width is 100 μm, the spacing between the two electrodes is 100 μm, and the size of the entire mask plate and the P++-Si substrate is 13×13 mm.
[0063] In this embodiment, the S-doped high-K oxide dielectric film is used as the dielectric layer of the thin film transistor. The S doping suppresses the increase of the low-frequency capacitance of the dielectric layer, thereby stabilizing the performance of the device.
[0064] In the present invention, the S-doped high-K oxide dielectric film has two main advantages:
[0065] (1) SO bond strength is relatively strong (521.7 kJ / mol), and no condensation reaction is required, SO4 2- Can bridge more than two cations; thus SO4 2- It can act as a stable network connector in the metal-oxygen framework;
[0066] (2) In the precursor solution, SO4 2- It has a strong complexing ability with metal cations and can replace the water ligands around the metal cations, thereby limiting the chance of -OH generation; during the annealing process, the precursor solution undergoes thermal hydrolysis, the water groups are converted into hydroxyl groups and oxygen ligands, and S is converted into SO4 2- Incorporation in the form of oxygen-containing anions can provide additional oxygen to the film and inhibit the formation of oxygen vacancies.
[0067] Therefore, S doping can reduce the oxygen vacancies and hydroxyl content in the dielectric film and promote the formation of the skeleton.
[0068] The present invention is further described in detail below with reference to the following embodiments.
[0069] Example 1
[0070] The preparation of the film in this embodiment uses heavily doped Si as the substrate, and the dielectric layer and active layer film are prepared by spin coating annealing. Taking the AlSOx film sample as an example, the specific preparation process is as follows:
[0071] (1) Prepare the precursor solution
[0072] High-purity aluminum nitrate nonahydrate powder (AlN3O9·9H2O, 99.9%, Sigma-Aldrich) was accurately weighed and dissolved in deionized water (DI Water), and a cleaned stirring bar was added. The stirrer was placed on a magnetic stirrer (model IKA C-MAG HS 7) and stirred at room temperature for 1-2 hours to obtain an aluminum nitrate nonahydrate solution.
[0073] Then, concentrated sulfuric acid (purity of 98%) was slowly dripped into the aluminum nitrate nonahydrate solution to obtain a precursor solution, wherein the concentration of the precursor solution was 1.5 mol / L, and the percentages of S / [Al+S] in the precursor solution were 0, 4, 8, 16, and 24%, respectively. Finally, five groups of precursor solutions with different S doping amounts were placed on a magnetic stirrer platform and stirred at room temperature for 5 hours.
[0074] (2) Preparation of AlSOx dielectric films
[0075] A 13×13 mm Si substrate (P-type heavily doped low-resistance silicon) was soaked in acetone, anhydrous ethanol, and ultrapure water and ultrasonically cleaned for 10 minutes in sequence; after cleaning, it was blown dry with nitrogen and placed in a plasma cleaning machine (model: DienerPlasma Atto) and treated with Plasma for 10 minutes in an appropriate oxygen atmosphere to enhance the surface hydrophilicity of the substrate and allow the precursor solution to be more evenly spin-coated on the substrate surface.
[0076] Afterwards, the prepared precursor solution was sucked up using a syringe, the needle was removed and a 0.2 μm injection filter was installed on the syringe, and then the precursor solution was dropped onto the substrate placed on a spin coater (model: Spin Master 51), and the coating was performed at a speed of 5000 rpm / s for 30 seconds.
[0077] After the coating process was completed, the sample was immediately placed on a heating table at 150°C for 5 min of pre-annealing. The annealing temperature was then raised to 350°C and a final annealing treatment was completed in an atmosphere for 1 h to obtain AlSO x Dielectric films.
[0078] (3) Evaporation electrode
[0079] The electrode of this embodiment is a 100 nm aluminum electrode deposited by thermal evaporation in the form of a mask plate, wherein the instrument model used is a high vacuum single-chamber thermal evaporation coating machine of YJ-ZF350A.
[0080] In order to verify the influence of the change of dielectric film performance on TFT devices, this embodiment further uses a solution method to prepare AlSO x The n-type oxide thin film transistor with In2O3 as the dielectric layer and In2O3 as the active layer; the metal electrode material selected is Al electrode; and the reason for selecting In2O3 as the active layer is that it has many advantages such as high mobility, easy preparation, and large bandgap width (3.65eV). X Schematic diagram of the preparation process of thin film transistor devices Figure 1 As shown, the specific process is as follows:
[0081] (1) Preparation of In2O3 thin films
[0082] First, a certain stoichiometric ratio of indium nitrate hydrate (lnN3O9·xH2O) powder was weighed and dissolved in deionized water, and the solution was placed on a magnetic stirrer and stirred at room temperature for 12 h to obtain a uniform In2O3 precursor solution with a concentration of 0.13 mol / L.
[0083] Then the prepared series of AlSO xThe films (S / [Al+S] percentages were 0, 4, 8, 16, and 24%, respectively) were placed in a plasma cleaner and the surface of the dielectric film was cleaned with oxygen plasma for 10 min. Finally, the AlSO X After the film was cleaned with a nitrogen gun and placed on a coater, a 0.2 μm filtered syringe filled with In2O3 precursor solution was used to drop the solution on the dielectric film and spin-coated at a speed of 5000 rpm / s for 30 seconds. The coater was then placed on an annealing table at 350°C for 1 hour.
[0084] (2) Evaporation electrode
[0085] After the active layer is prepared, the mask plate can be attached to the sample using high temperature resistant polyimide tape, and an aluminum electrode of about 100 nm is deposited on the surface of the active layer using thermal evaporation deposition, finally preparing Al / In2O3 / AlSO X / P++-Si structure bottom gate top contact TFT device. The length of the prepared electrode is 1500μm, the width is 100μm, the spacing between the two electrodes is 100μm, and the size of the entire mask plate and the substrate P++-Si is 13×13mm.
[0086] The AlSO prepared in this example x Dielectric films and Al / In2O3 / AlSO X The performance of the bottom-gate top-contact TFT device with P++-Si structure is tested as follows:
[0087] (1)AlSO x Characterization and analysis of dielectric films
[0088] GIXRD test is used to understand the crystallinity of the doped film, such as Figure 2 As shown in (a), all S-doped AlSO prepared by annealing at 350℃ x The dielectric film has no obvious diffraction peaks, and the peaks at 20-30° belong to the glass substrate. For the dielectric layer in the TFT structure, the amorphous layer is ideal, because the grain boundary can act as a short-circuit diffusion path, which can easily serve as a channel for impurity diffusion and leakage current, resulting in a decrease in the breakdown electric field of the dielectric layer and an increase in the leakage voltage.
[0089] Figure 2 (b) shows the AFM test image of the series of films. The image shows the changes in the surface morphology of the dielectric layer film after doping. The scanning area is 4×4μm. x The root mean square roughness (RMS) of the dielectric film is less than 0.2nm. xThe RMS value of the dielectric film remains at a very low level, which proves that the addition of S does not destroy the smooth AlSO x Dielectric films.
[0090] Through ellipsometer test fitting, a series of AlSO x The thickness of the films are 70.87±0.024, 71.60±0.015, 76.22±0.017, 77.13±0.017 and 78.09±0.017nm respectively. x The refractive index of the film-incident light wavelength curve (such as Figure 2 As shown in (c) in the figure, it can be seen that with the increase of S doping amount, AlSO x The refractive index of the film (@550nm) increases first and then decreases, and its values are 1.476, 1.490, 1.559, 1.549, and 1.514, respectively. The relative density of the film can be calculated according to the Yoldas formula, so as to obtain the relative densification degree of the film, and the formula is as follows:
[0091] in
[0092] Among them, n, n1, and n2 are AlSO X The refractive index of the film, the refractive index of the bulk Al2O3 (n1 = 1.762), the number of voids (air or water) retained in the film, ρ, ρ1, ρ2 are respectively AlSO X The film density of the film and the density of the bulk Al2O3 (ρ1 = 4.00 g / cm 3 ), the void density (air or water) retained in the film. It can be found that the volume fraction q1 depends largely on the type of pores. Because this series of films were annealed at 350°C, the pore type of the film is air (n2 = 1, ρ2 = 0 g / cm 3 ) in the form of. Therefore, the relative densities calculated by the Yoldas formula are 2.875, 2.935, 3.220, 3.180, and 3.035 g / cm 3 It is obvious that with the increase of S doping amount, the calculated relative density increases first and then decreases. Among them, the maximum density of the film doped with 8at% S is 3.220g / cm 3 Therefore, proper S doping makes the solution-prepared Al2O3 dielectric layer form a denser film.
[0093] Figure 2 (d) is the FTIR spectrum of the series of precursor powders. -1The broad absorption band centered at 1640 cm -1 The low-intensity absorption bands on the left and right are the OH stretching vibration peak and the HOH bending mode vibration peak. The intensity of these two characteristic peaks related to hydroxyl groups first decreases and then increases. Among them, the intensity of 8at% S doping is the smallest, which indicates that the hydroxyl content in the relevant film also increases first and then decreases. -1 The vibration peak comes from trace NO3 - The vibration intensity gradually decreases with the increase of doping amount, which is related to the reduction of aluminum nitrate solute after doping and the increasing SO4 2- (1130cm -1 The vibration modes in the FTIR spectrum of sulfate groups include not only 960-1280cm -1 Strong vibration mode, still at 584-712cm -1 The weak vibration band of SO4 2- In addition, 610cm -1 The vibration peak centered on is the superposition of the vibration modes of the Al-O and SO bonds.
[0094] Figure 2 (e) shows AlSO with different doping concentrations. X UV-Vis spectra of dielectric films, where the inset in (e) is the corresponding bandgap width. The optical bandgap of the film can be fitted by the standard Tauc plot method. It can be found that as the S doping amount increases, the bandgap gradually increases. The AlSO doping amount of 0, 4, 8, 16, and 24 at% increases. X The corresponding optical band gap values of the films are 5.09, 5.30, 5.40, 5.44 and 5.60 eV respectively. Defects in the film will produce localized states in the band gap, resulting in a decrease in the band gap energy. A large band gap also reflects the high quality of the film formation. In addition, Figure 2 The weak absorption phenomenon in the sub-bandgap region (3-4 eV) shown in (e) is caused by oxygen vacancy defects. Figure 2 (f) in the figure shows the corresponding absorption coefficient spectrum. As shown in the figure, S doping will reduce the absorption coefficient α of the film in the sub-bandgap region. It can be inferred that S doping can reduce the defects in the form of oxygen vacancies in Al2O3 films.
[0095] Figure 3 (a) and (b) are AlSO with 0 and 8 at% S, respectively. X TG-DTG curve corresponding to the precursor powder. It can be observed that the maximum rate of weight loss is at about 200°C. This means that the formation of Al-O and SO as the skeleton begins, and all dehydration processes are completed at this time. 8at%S AlSOX The mass loss of the precursor powder during heating from 200°C to 376°C comes from the loss of hydroxyl and nitrate ions, at which time the MOM (M is Al or S) skeleton has been fully formed. The undoped precursor powder completes this mass loss process when heated to 489°C, indicating that S doping can reduce the dehydroxylation temperature of the Al2O3 film. In addition, there is a 4.43% mass loss process in the temperature range of 785°C to 958°C, which is due to the gradual escape of S from the film in the form of SO2.
[0096] like Figure 4 As shown, this series AlSO X The XPS spectrum test of the film deeply explores the composition changes of the film after doping. Among them, the peak spectra obtained by the test have been calibrated with the standard C1s peak. Figure 4 (a) shows the series AlSO X The peak fitting of the O1s core energy level spectrum in the film is decomposed into three sub-peaks by convolution, and the sub-peaks are centered at 531eV, 532.3eV and 532.9eV respectively. These sub-peaks correspond to the metal oxygen (Al-O) formed by combining with aluminum, the hydroxide (M-OH) and vacancy oxygen (Ov) formed with S and Al, and the oxygen (SO) formed by combining with S to form a sulfate network. Such peak selection of O1s spectrum peak is related to the electronegativity of Al (1.61), H (2.20), and S (2.58).
[0097] according to Figure 4 (a) The O 1s peak in the film shows that as the S doping amount increases from 0at% to 24at%, the center of the O 1s peak gradually moves 1.1eV toward the high binding energy direction. As we all know, electrons at the core energy level are not only affected by the Coulomb force of the nucleus, but also by the outer electron density. Generally speaking, the greater the outer electron density, the lower the binding energy position of the corresponding atom's peak. Obviously, the order of giving electrons to oxygen ions is Al>H>S. Therefore, as the S doping amount increases, the Al-O content in the film gradually decreases, and the SO content gradually increases, which causes the outer electron density of oxygen to gradually decrease. This causes the O1s peak position to gradually move toward the high binding energy direction.
[0098] Table 1 shows the area ratios of the three convolution peaks to the total O1s peak, and plots them as Figure 4 As shown in (b) in the figure, it can be found that with the increase of S doping, the content of Al-O first increases and then decreases. Its content first increases because of the connection effect of the sulfate network, which reduces oxygen vacancies and makes Al-O formation more complete. The reason why its content decreases later is that with the continuous incorporation of S, the solute of the Al2O3 ratio continues to decrease and the filling of oxygen vacancies gradually tends to saturation. Figure 4(b) in the figure also shows that as the S doping amount increases, the content of M-OH and oxygen vacancies first decreases and then increases. This is because as the S doping amount increases, after the reduction of oxygen vacancies and hydroxyls reaches a certain saturation, the sulfate ions that are not connected to the metal oxygen skeleton will bring defects. For example, it makes the surface of the film have strong hygroscopicity, provides active sites, and increases the number of hydroxyls. Among them, when the S doping amount is 8at%, the content of M-OH and oxygen vacancies is the lowest (22.1%). This is also consistent with the results of the FTIR spectrum. The hydroxyl content in the film shows a trend of first decreasing and then increasing.
[0099] Table 1 AlSO with different S doping amounts X O 1s peak fitting value of thin film
[0100]
[0101] Figure 4 (c) shows AlSO with different S doping amounts. X The Al 2p core energy level spectrum peak of the film. The results show that with the increase of S doping, the binding energy of the Al 2p spectrum peak increases from 74.6eV to 75.2eV, which proves that the chemical environment around Al has changed. The reason is that the metal oxygen skeleton is formed more fully, which reduces the outer electron density of aluminum ions and weakens the electron shielding effect, thereby increasing the binding energy.
[0102] Figure 4 (d) shows the core energy level spectrum peak of S2p. It can be seen that the center position of its characteristic peak is basically at 170eV, proving that the S atom exists in the film in the form of positive hexavalent (surrounded by four oxygen atoms), and there are no characteristic peaks at other positions, especially without S 2 - characteristic peak (162eV), that is, there is no S 6+ The existence of other valence forms.
[0103] Figure 4 (e) in the figure is the atomic ratio of S / [S+Al] in the film quantitatively analyzed by the peak area of X-ray photoelectron spectroscopy, and its values are 0, 4.25, 8.12, 14.54 and 23.47 at%, respectively, which is basically consistent with the doping ratio of the precursor configured previously, indicating that S atoms are basically incorporated into the Al2O3 structure.
[0104] like Figure 5 As shown, AlSO with S doping content of 0at% and 8at% X Three-dimensional dynamic flight secondary ion mass spectrometry, i.e. 3D-TOF-SIMS. From this, the relative content changes of H, Al, and S from the film surface to the substrate can be obtained. Among them, the relevant ion content of the Al2O3 film with 0at% S is used as the standard sample. Figure 5 (a) shows the H + The relative content changes with etching time. The results show that the H + The content of hydroxyl groups decreased significantly, which is consistent with the decrease of hydroxyl content in the previous XPS test and infrared spectrum analysis. + The content is related to the adsorbed water caused by hydroxyl groups and oxygen vacancies. In addition, the SIMS curves of the 0at%S and 8at%S dielectric films obtained by the test showed a significant decrease at etching times of 130 and 95 seconds, respectively, which means that the etching of the dielectric layer has ended. The reason for the different etching end times is that the changes in the film doping lead to different etching speeds.
[0105] like Figure 5 As shown in (b) and (c), it is Al 3+ and S 6+ The relationship between the relative content of AlSO and the etching time. x Al in thin film 3+ The content of S in the undoped Al2O3 film is lower than that in the undoped film. This is because when S doping is performed, the proportion of Al2O3 solute is reduced proportionally. 6+ The content curve of S has a downward process, which means that the S element has been detected. The reason is that the detection end receives the S 6+ Ion fragments with the same charge-to-mass ratio. Figure 5 (d) and (e) in the figure are the corresponding 3D renderings, which intuitively show the relative content and distribution of each ion from the film surface to the depth of the substrate. X The film represents H + The number of red dots is very large and dense, while the 8at%S AlSO X The film has a significant reduction compared with that of the film, which directly proves that H + In addition, the dark green dots represent the Si element detected in the substrate, indicating that the ion content and distribution throughout the film were obtained from the surface etching to the substrate.
[0106] 27 Al nuclear magnetic resonance spectroscopy (NMR) can be used to detect the coordination environment of Al in the film. Figure 6 (a), (b), and (c) show different S doping amounts. 27 The Al NMR curve shows that the peaks at 5, 35, and 72 ppm represent the three coordination environments formed by Al and O: octahedral (Al(O)6), pentahedral (Al(O)5), and tetrahedral (Al(O)4). By integrating these three peaks, the proportions of the three coordination modes in each film can be obtained (e.g. Figure 6 As shown in (d) in the figure, the results show that after S doping, the Al(O)6 coordination ratio in the film increases, the Al(O)5 coordination ratio decreases, and the Al(O)4 coordination ratio remains basically unchanged. The conversion of Al(O)4 and Al(O)5 to the Al(O)6 coordination mode can effectively suppress ion polarization, thereby suppressing dielectric dispersion in traditional dielectric materials. Therefore, S doping can suppress H + This is consistent with the H + In addition, Al(O)5 ligands are usually surrounded by an oxygen vacancy defect. The Al(O)5 ligand content in the S-doped film is significantly reduced, which also proves that the reduction of oxygen vacancies in the film promotes the formation of high-quality films.
[0107] (2) Effect of doping on AlSO x Mechanism analysis of film effects
[0108] When metal nitrate powder is dissolved in water, the metal cations will be solvated by water molecules to form metal water complexes. Therefore, when aluminum nitrate is dissolved in deionized water, the aluminum cations and the hexahydrate ligands will form the corresponding complex, namely Al[(OH2)6] (such as Figure 7 As shown in (a) in 7). It has been proved that the film forms a metal oxygen skeleton (Al-O-Al) after annealing, but there are still some hydroxyl groups and oxygen vacancies, as shown in the network diagram of (a) in 7. According to the previous FTIR and XPS analysis results, S exists in the film in the form of sulfate. In the configured solution, SO4 2- Can replace water ligands and bind to adjacent Al 3+ It has a high complexing ability and forms Al[(OH2)4(HSO4)] complex. In the post-annealing process, SO4 2- It can survive thermal annealing and act as a network former, making the oxide framework denser (e.g. Figure 7 As shown in (b) in the figure). Among them, SO4 2- As oxygen-containing anions, they can provide additional oxygen to the film, which can also be reflected in the change of film thickness. The film thickness of the previous ellipsometry test gradually increases with the increase of S doping amount. 2- The ionic radius (140 pm) is smaller than that of S 6+ (37pm) and Al 3+ (53.5 pm) is larger than the ion radius, so the film thickness increases slightly after doping. In summary, S doping into Al2O3 film mainly plays two roles: one is to fill the oxygen vacancies in the film, and the other is to eliminate a large number of hydroxyl groups and connect the metal oxygen skeleton. This makes the film denser and the content of free hydrogen ions that can be generated is also reduced. Among them, the AlSO before and after dopingX The schematic diagram of the metal network fragment in the amorphous film can vividly describe the effect of S doping.
[0109] (3)AlSO x Analysis of Bias Capacitance Characteristics of Thin Films
[0110] Figure 8 (a) in the figure depicts AlSO X The capacitance of the film changes with frequency under 0V, 1V, and 2V bias voltages. For intuitive comparison, the capacitance of each frequency can be gathered on the same horizontal axis (such as Figure 8 , and the corresponding dielectric constant (as shown in (b) in Figure 8 (c) in Figure 1). The test frequency range is 20 Hz to 300 kHz. It can be found that the capacitance of all dielectric films in the high-frequency stage (>1000 Hz) with or without bias is relatively stable, and its value is independent of the doping concentration and bias voltage. This is because the polarization effect changes and the space charge cannot respond to the high-frequency electric field.
[0111] like Figure 8 As shown, 0at% S-AlSO X As the bias voltage of the film increases (0V-Bias→1V-Bias→2V-Bias), the capacitance distribution range of the film gradually increases (102~165nF / cm 2 →104~216nF / cm 2 →108~325nF / cm 2 ), the calculated dielectric constant distribution range is also gradually increasing (8.1~13.1→8.2~17.1→8.6~25.8). Among them, the increase in the distribution range is mainly due to the contribution of the increase in low-frequency capacitance, and the greater the bias voltage, the greater the 0at% S-AlSO X The thin film low frequency capacitor is more unstable and larger. Figure 8 As shown in (b) and (c), under 2V bias, the S-doped AlSO X The capacitance and dielectric constant of the film are reduced to varying degrees. X The film has the most stable capacitance in the entire frequency range. X As the bias voltage increases (0V-Bias→1V-Bias→2V-Bias), the capacitance range of the film does not change significantly (110~131nF / cm 2 →105~135nF / cm 2 →107~140nF / cm 2), the calculated dielectric constant value changes slightly (9.5~11.2→9.0~11.6→9.2~12.1), which is roughly equivalent to the dielectric constant value of typical Al2O3 films. From the above results, it can be seen that appropriate S doping will make AlSO X The low-frequency capacitance of the film is more stable, that is, the AlSO X Capacitance-frequency dependence of dielectric films.
[0112] The capacitance-frequency dependence is related to the double-layer capacitance EDL formed between the dielectric film and the electrode, and generally occurs in the low-frequency capacitance stage. In fact, the additional capacitance generated can be called pseudo-capacitance, which is difficult to control artificially and is an unstable factor. The principle of its generation is that after the bias voltage is loaded, an electrochemical reaction occurs on the contact surface between the dielectric film and the electrode. Under the action of the electric field, the free ions can move to the interface between the electrode and the dielectric film, resulting in the accumulation of electrostatic charge to form a pseudo-capacitance. The value of the pseudo-capacitance is mainly related to the size of the bias voltage and the free H in the film. + The free ions in the film are mainly H + , and the adsorbed water caused by hydroxyl groups and oxygen vacancies will contribute to the mobile H + Therefore, the capacitance-frequency dependence is suppressed, which is attributed to the reduction of hydroxyl groups and oxygen vacancies in the film after S doping.
[0113] (4)AlSO x Analysis of leakage current characteristics of thin films
[0114] In order to explore the effect of S doping on the dielectric properties of Al2O3 thin films, Al / AlSO X / p++-Si MIM structure samples were tested for leakage current density (J leak ) and the electric field (E) (e.g. Fig. 9 As shown in (a) in Figure 2, it can be seen that the AlSO with doping amounts of 0, 4, 8, 16, and 24 at% S x When the unit electric field strength of the dielectric film is 2MV / cm, the leakage current of the film is 5.68×10 -7 , 3.02×10 -7 , 1.05×10 -7 , 1.46×10 -7 4.03×10 -7 A / cm 2, indicating that the dielectric properties of Al2O3 film at low electric field strength are improved after S doping. The essential reason comes from the reduction of the relative content of hydroxyl and oxygen vacancies, because the existence of these defects may serve as carriers of leakage current. When the electric field strength is in the high electric field region (>2MV / cm), the leakage current of Al2O3 film begins to increase significantly, and breakdown occurs near the 3MV / cm electric field. AlSO after S doping X The leakage current value of the film in the high electric field region is significantly reduced, and the 8at%S AlSO X The breakdown electric field strength of the film is increased to 7.25MV / cm.
[0115] like Fig. 9 As shown in (b), it is a series of AlSO X The breakdown field strength statistics of 20 electrode points in the film can verify the AlSO X It can be clearly seen from this figure that with the increase of S doping, AlSO X The breakdown field strength of the film shows an improvement pattern of first increasing and then decreasing. The breakdown of the dielectric film means the transition of the film from an insulating state to a conductive state, and this process is irreversible, that is, the damage of the device. Therefore, a larger breakdown field strength allows the device based on the dielectric layer to have a larger safe operating range. Obviously, appropriate S doping has greatly improved its related performance.
[0116] In order to further explore the mechanism of improved leakage current performance after doping, the effect of S doping on the leakage current conduction mechanism of dielectric films was studied. The conduction mechanism of Al2O3 insulators is mainly divided into two effects: Schottky effect (SE) and Poole-Frenkel effect (PF). Among them, the SE effect generally occurs in low electric field strength and is more likely to occur in dielectric layers with fewer defect states. The PF effect is a conduction process controlled by the bulk volume, which is highly dependent on the contribution of defects in the entire bulk dielectric layer. Their current density expressions are:
[0117] Schottky effect (SE):
[0118] Poole-Frenkel effect (PF): Where J is the current density, A* is the Richardson constant (120m* / m0), T is the absolute temperature, and q is the electron charge (1.602×10 -19 C), is the barrier height, k B is the Boltzmann constant (1.38×10 -23 J / K), E is the electric field strength, ε0 is the dielectric constant of free space (8.854×10 -14 F / cm), ε dis the dynamic dielectric constant (i.e. the square of the refractive index, n 2 ).
[0119] From the SE and PF formulas, we can find two linear relationships between them, namely, ln(J / T 2 )vs.E 1 / 2 andln(J / E)vs.E 1 / 2 Thus, the series of JE curves are converted into linear relationship curves (such as Fig. 9 As shown in (c) and (d) in Figure 1, it can be observed that the low electric field region in the SE mechanism curve is linear, and the high electric field region in the PF mechanism curve is linear. Therefore, the low electric field region and the high electric field region can be assigned to the SE and PF mechanisms respectively. The middle area of the electric field is the area where the two mechanisms work together and the two mechanisms transform.
[0120] Substituting the slope of the fitting curve into the SE formula, the AlSO with doping amounts of 0 and 8 at% S was calculated. X The barrier height between the dielectric film and the Al electrode is 1.709 and 1.747 eV respectively (where the effective mass of the dielectric layer m*=0.35m0). According to previous studies, when the barrier height is greater than 1.5 eV, it is sufficient to suppress the thermal ion current and reduce the leakage current under room temperature working conditions. X The films all meet this condition and the barrier height is further improved after S doping. Fig. 9 The linear fitting part of the PF mechanism shown in (d) has changed, and the maintenance of the PF conduction mechanism depends on the amount of traps in the bulk film and is related to the dielectric film itself. In summary, S doping improves the leakage current performance of Al2O3 because the role of the leakage current mechanism in the film has changed to a certain extent.
[0121] (5) In2O3 / AlSO X Characterization and analysis of TFT devices
[0122] Fig.10 (a) is In2O3 / AlSO X Schematic diagram of the (8at%S) TFT device structure, from bottom to top: P++-Si layer, AlSO X layer, In2O3 layer and aluminum electrode; Fig.10 (b) shows In2O3 / AlSO X / P++-Si cross-section diagram, where the S doping amount is 8at%. It can be found that the levels of each interface are very clear, and there is no obvious interface mutual dissolution and atomic diffusion phenomenon, and no hole-shaped or hill-shaped defect structure. Fig.10(c) is a high-resolution image of the ln2O3 layer, which shows that it has very good crystal quality, and the atoms and crystal planes are arranged very neatly, which is conducive to the stable transmission of carriers. Among them, the calibrated crystal plane displayed is (222), the interplanar spacing between the two crystal planes is 0.29nm, and the overall thickness is roughly calculated to be 3nm. Fig.10 (d) in the figure is the corresponding fast Fourier transform pattern (FFT), revealing the well-defined nanocrystalline ln2O3 structure.
[0123] The carriers generated when the device is working will gather at the interface between the dielectric layer and the active layer, so it is necessary to understand the composition uniformity of the surface of the dielectric film after doping. Fig.10 As shown in (e), it is 8at%S AlSO X EDS spectrum of the film and element surface scanning distribution. The elements contained on the surface of the film are Al, S, O, and N. Their distribution on the surface of the film is uniform, which is conducive to the transmission of carriers. Among them, the content of N is very small, which means that although the film still contains nitrate ions at the annealing temperature of 350°C, it is actually a very small amount and can be ignored. The percentages of Al and S are 33.44% and 3.15% respectively. The calculated S / [Al+S] content ratio is 8.61%, which is basically consistent with the previous quantitative analysis of the atomic ratio of S / [S+Al] in the film (8.12%) by the peak area of X-ray photoelectron spectroscopy, and is also consistent with the stoichiometric ratio of 8at% S in the precursor.
[0124] (6) In2O3 / AlSO X Performance Analysis of TFT Devices
[0125] Fig.11 As shown in (a) and (b), the series In2O3 / AlSO X The transfer and output curves of the TFT device and its corresponding performance parameters are shown in Table 2. Fig.11 (a) shows that appropriate doping can make the corresponding device have a larger on-off ratio. The on-off ratio of the Al2O3 TFT device is only 1.15×10 3 This is obviously far from the ideal switch ratio. This is mainly because the active layer material (ln2O3) itself has a relatively excessive carrier concentration, making it difficult to effectively limit the leakage current. X The film has better compactness and fewer defect states, which makes it difficult for the channel current of the TFT device to leak from the channel layer to the gate. Therefore, the off-state current of the device is reduced and the switch ratio is increased. Among them, the switch ratio of the device corresponding to the S doping amount of 8at% is the largest, which is 2.53×10 6 This value is higher than that of similar devices studied by previous researchers (lnBO / AlBO, Ion / I off >10 5 ), and achieve the switching ratio required for practical application.
[0126] By calculation, the ln2O3 / AlSO with S doping content of 0, 4, 8, 16, and 24 at% can be obtained. X Interface defect state density of TFT devices. Among them, the corresponding device with 8at% S has the smallest interface defect state density, which directly proves that appropriate S doping reduces the defects of dielectric films. At the same time, the subthreshold swing (SS) of positive and negative scans is also calculated, and their corresponding sizes show a trend of first decreasing and then increasing with the increase of doping concentration. Generally speaking, the SS value is determined by the interface quality of the active layer and the dielectric layer, and characterizes the current change rate of the device switching between the off state and the on state. The lower the SS value, the smaller the corresponding gate voltage required for a unit increase in drain current, and the stronger the control ability of the device. Obviously, appropriate S doping can improve the control ability of the device. Among them, the corresponding device with 8at% S has the smallest SS value (0.14V dec -1 ).
[0127] Table 2 In2O3 / AlSO with different doping concentrations X TFT device performance parameter table
[0128]
[0129] pass Fig.11 It can be found in (a) that the forward and reverse sweep curves of the entire series are highly overlapped, which reflects the good stability of the device. The reason is that the interface between the active layer and the dielectric layer of this series of devices has a high quality, and the phenomenon of carrier capture by electron traps under zero gate bias is not obvious. According to I ds 1 / 2 About V gs The tangent line of the curve gets its corresponding V TH ,like Fig.11 As described in (a), V TH The specific values of are shown in Table 2. TH | value allows the device to be turned on and off at a lower operating voltage, with a stable |V TH | value is conducive to the use of device integration. In previous research, the |V TH | are relatively large, some even exceed 10V. The |V TH | value is generally greater than 0.2V. XThe |V TH | are close to zero. Therefore, this has important guiding significance for the preparation of low-power and highly integrated devices. Fig.11 As shown in the output curve (b) in Figure 1, the saturated output current gradually decreases with the increase of S doping amount. This is because the decrease of pseudo capacitance reduces the accumulation of carriers at the interface.
[0130] Table 3 shows In2O3 / AlSO X Mobility statistics of TFT devices. In order to compare the deviation caused by using different capacitances to calculate mobility, we define the mobility deviation value μ*=((μ sat(10 4 Hz) -μ sat(20Hz) ) / μ sat(20Hz) ). The capacitance values are all obtained under a bias voltage of 2V. The μ* values calculated for S doping amounts of 0, 4, 8, 16 and 24 at% are 183%, 74%, 26%, 45% and 51% respectively. Obviously, if the capacitance obtained at a higher frequency (>100Hz) and under no bias is used to calculate the mobility, it will be much larger than the actual mobility, which leads to a significant overestimation of the mobility. In fact, when studying ZnlnSnO / Al2O3TFT devices in an article, the capacitance of the dielectric layer is 10 4 The stable capacitance at Hz frequency has a mobility of 117cm 2 V -1 s -1 Therefore, the capacitance under 2VBias-20Hz is used to calculate the mobility of the series devices, and its value increases first and then decreases. It can be seen that appropriate S doping can also improve the mobility performance of the corresponding TFT device, which is due to the improvement of the dielectric properties of the dielectric film. From the perspective of comprehensive performance, the device with the best comprehensive performance is 8at%S In2O3 / AlSO X TFT, whose μ is 20.6cm 2 V -1 s -1 , I on / I off 2.53×10 6 , SS value is 0.14V dec -1 , V TH is 0.06 V. Compared with previous related studies, the apparent mobility calculated in this embodiment is more realistic and reduces the influence of the capacitance-frequency dependence characteristic.
[0131] Table 3 Series In2O3 / AlSO X Numerical statistics of TFT device mobility under different bias voltages and frequency capacitances
[0132]
[0133] (7) In2O3 / AlSO X Bias stability test of TFT devices
[0134] Fig.12 Shown is ln2O3 / AlSO X The bias stability test of TFT devices can be used to evaluate the stability of TFT devices under repeated positive bias stress (PBS) and negative bias stress (NBS) working environments. This series of transfer curves is obtained by applying a 5V positive gate bias or negative gate bias to the same device, and taking bias durations of 0, 80, 160, 320, 640, 1280, and 2560 seconds for continuous testing. Among them, the S source used is sulfuric acid, and the dielectric film is annealed at 350°C. Fig.12 (a) and (b) show the PBS test curves of 0 and 8 at% S TFT devices. It can be found that as the bias time increases, the magnitude of the positive shift of the transfer curve increases. Among them, when the bias time is 2560 seconds, the threshold voltage of the TFT device with 0 and 8 at% S doping is positively shifted by 1.51 and 0.51 V respectively (as shown in Figure 2). Fig.12 (c) in the figure). The fundamental reason for this phenomenon is the reduction in effective carrier concentration. According to previous reports, the threshold voltage shift phenomenon of non-passivated TFT devices under PBS is attributed to the carriers being captured by the interface of the dielectric layer / active layer or defects in the dielectric layer during transmission. Obviously, the amplitude of the positive shift of the threshold voltage of the TFT device with a S doping amount of 8at% is smaller than that of the undoped Al2O3 film. This shows that after S doping, the dielectric film becomes denser, which improves the PBS stability of the device.
[0135] like Fig.12 (d) and (e) show the NBS test curves of 0 and 8 at% S TFT devices. It can be found that as the bias time increases, the magnitude of the negative shift of the transfer curve increases. Among them, when the bias time is 2560 seconds, the threshold voltage of the TFT device with 0 and 8 at% S doping is negatively shifted by 1.83 and 0.82 V (as shown in Figure 2). Fig.12 The on-state current also increases with the loading time of the bias gate voltage. This phenomenon is consistent with the typical capacitance-frequency dependence. The continuous loading bias causes the free H in the film to +The pseudo capacitance is generated by the aggregation under the ln2O3 layer, which increases the capacitance per unit area under stress, thereby enhancing the carrier response, resulting in a negative shift in the transfer curve and an increase in the on-state current. The reduction in the negative shift of the threshold voltage of the device after S doping indicates that S doping can inhibit the mobile H in the Al2O3 dielectric layer. + The device response is unstable, which improves the NBS stability of the device.
[0136] Example 2
[0137] Based on AlSO annealing temperature at 250℃ X Characterization of thin film and TFT device performance
[0138] In order to verify the feasibility of the S doping method at a lower annealing temperature, this example investigates the AlSO with 0 and 8 at% S after annealing at 250 °C. X Thin films and TFT devices, and a series of characterizations have been made. Fig.13 As shown in the leakage current characteristic curve (a) in Figure 1, after S doping, the film shows an improvement in leakage current at low electric field strength and an increase in breakdown field strength (3.89→5.89MV / cm). Fig.13 As shown in (b) in the figure, in the absence of bias, the film exhibits a capacitance-frequency dependence, which is more obvious under a 2V bias (as shown in Fig.13 In particular, for AlSO with 0 at% S X For film, its low frequency capacitance at 20Hz (552nF / cm 2 )For high frequency capacitance (91nF / cm 2 ) increased by 461nF / cm 2 , while 8at%S AlSO X The film showed a more stable performance (185→91nF / cm 2 ). This shows that under 250℃ annealing, S doping can also suppress the capacitance-frequency dependence of Al2O3 dielectric films, and this effect is more obvious.
[0139] Fig.13 (d) is ln2O3 / AlSO X The transfer characteristic curve of the device, Fig.13 (e) and (f) are ln2O3 / AlSO with 0 and 8 at% S X Table 4 shows the output curve of the device. X Performance parameters of TFT devices; it can be found that the performance of the corresponding TFT devices has been improved after S doping, and the mobility has also been greatly improved (0.25→6.66cm 2 V-1 s -1 Table 5 shows the statistics of relevant mobility parameters; it can be found that at a bias voltage of 2V, 0at%S of ln2O3 / AlSO X The device exhibits a clear mobility-frequency dependence. The mobility calculated at 1000 Hz (1.43 cm 2 V -1 s -1 ) compared to the mobility calculated at 20 Hz (0.25 cm 2 V -1 s -1 ) increased by 472%, corresponding to 8at%S AlSO X / ln2O3 device only increased by 103%. This shows that the incorporation of S inhibits the increase of the low-frequency capacitance of the dielectric layer, thereby stabilizing the performance of the device.
[0140] Table 4 In2O3 / AlSO based on 250℃ annealing temperature X TFT device performance parameter table
[0141]
[0142] Table 5 In2O3 / AlSO based on 250℃ annealing temperature X Statistics of mobility parameters of TFT devices at different capacitance frequencies under different bias voltages
[0143]
[0144] Example 3
[0145] In this example, N2O7Zr·xH2O, Ga(NO3)3·xH2O, N3O9Sc·xH2O, N3O9Ho·xH2O, and N3O9Sm·6H2O powders were used to prepare the relevant solutions. Sulfuric acid was used as the sulfur source for S doping, and ZrSO with different S contents were prepared. X (1.5mol / L), GaSO X (1.5mol / L), ScSO X (1.5mol / L), HoSO X (1mol / L), SmSO X (1 mol / L) precursor solution. The percentage of S / [S+Zr] is 0, 5, 10, 15 and 20 at%, and the percentage of other dielectric materials is 0 and 10 at%. Except for this, the rest of the preparation method is the same as that of Example 1.
[0146] Finally, the S-doping method was adopted to prepare ZrSO X 、GaSO XScSO X 、HoSO X 、SmSO X Five representative dielectric films are studied; their microstructures, leakage currents, and bias capacitances are analyzed in detail. The conclusions are as follows:
[0147] Fig.14 ZrSO X GIXRD patterns of the films, where all series of ZrSO X The only characteristic peak that appears in the dielectric film is the crystallization peak of the silicon substrate, indicating that the ZrSO X All are amorphous;
[0148] like Fig.15 Shown are ZrSO with different S doping amounts X AFM images of the film, the scanned morphology area is 2×2μm. ZrSO doped with S content of 0, 5, 10, 15 and 20at% X The root mean square roughness (r q ) values are 0.170, 0.106, 0.134, 0.174 and 0.209 nm respectively.
[0149] Fig.16 The ZrSO with different doping concentrations is given. X The XPS spectrum of the film and its peak fitting results. Table 6 shows the three sub-peaks of the O1s convolution decomposition, which correspond to the Zr-O peak at 531eV, the M-OH peak at 532.3eV, and the SO peak at 532.9eV (where M can be Zr or S). The selection of the peaks also comes from the electronegativity of Zr, S, and H. Fig.16 As shown in (a), the position of the O 1s peak gradually moves toward the direction of high binding energy as the amount of S doping increases, which corresponds to the increase in the proportion of sulfur-oxygen bonding at the high binding energy position. This phenomenon also corresponds to the S doping content tested by XPS (e.g. Fig.16 As shown in (e) in Fig.16 As shown in (d), Zr 3d 5 / 2 and Zr 3d 3 / 2 The orbital peak spacing has not changed, but it has moved to a higher binding energy position overall. This is because the metal oxygen skeleton is more fully formed and the H on Zr-OH is replaced by S, which reduces the outer electron density of the zirconium ion and weakens the electron shielding effect, thereby increasing the binding energy. Fig.16(c) shows the core energy level spectrum peak of S2p, the center position of its binding energy is around 169eV, and there are no other peaks between 158 and 174eV. The peaks of sulfur ions in other valence states, such as negative divalent, positive divalent, and positive tetravalent sulfur, are all between 158 and 164eV in the XPS spectrum, which indicates that the existence form of the doped S is only positive hexavalent, and does not exist in other valence states. Table 6 and Fig.16 (b) shows that the proportion of residual hydroxyl content in the film is reduced after S doping. Among them, the relative content of hydroxyl and oxygen vacancies is the highest (51.2%) when the S doping amount is 0at%, and the lowest (28.4%) when the S doping amount is 10at%. The corresponding MOM skeleton in the film is the highest (71.6%) when the S doping amount is 10at%. Obviously, the appropriate S doping amount promotes the formation of the skeleton in the film and reduces the hydroxyl and oxygen vacancies that exist in the form of defects.
[0150] Fig.17 (a) is ZrSO X Capacitance-frequency curves of a series of films under 2V bias. This series of films has obvious capacitance instability at low frequencies below 100Hz. Among them, the capacitance of the undoped S film has the largest amplitude of scattered distribution. 0, 5, 10, 15, 20at% S-doped ZrSO X The capacitance values of the series films in the stable stage of the curve are 291, 264, 219, 216, and 213 nF / cm 2 On this basis, the calculated mobility deviation values μ* are 81.4%, 42.0%, 30.1%, 36.1% and 42.7% respectively. Fig.17 The inset in (a) shows the dielectric constants for all frequency ranges for each doping concentration. X The capacitance corresponding to each frequency under the bias of the film is relatively concentrated, and its value is about 15. In general, proper S doping has a stabilizing effect on the biased low-frequency capacitance of ZrO2. S enters the film in the form of oxygen-containing anions, connecting the metal oxygen skeleton, filling oxygen vacancies and eliminating hydroxyl groups to form a more stable structure. This inhibits the formation of free hydrogen ions, making the low-frequency capacitance under bias more stable.
[0151] Table 6 ZrSO with different S doping amounts X The area value of the O 1s peak fitting of the film
[0152]
[0153] Fig.17(b) is the leakage current characteristic curve of the series of thin films. When the electric field strength is 7MV / cm, 0, 5, 10, 15, 20at% S-doped ZrSO X The leakage current density of the film is 1.4×10 -5 , 8.5×10 -7 , 3.9×10 -7 , 1.6×10 -6 , 1.5×10 -3 A / cm 2 With proper S doping, the unit breakdown electric field strength of the dielectric film is increased from 6.57 MV / cm (0at%) to 10.56 MV / cm (10at%). However, excessive S doping leads to a sharp increase in the leakage current of the corresponding film, because excessive sulfate ions become impurities, destroying the original dense structure, thereby increasing more electron escape pathways.
[0154] like Fig.18 The transfer and output curves of the prepared device are shown in Table 7. The electrical performance parameters obtained from the transfer curves are listed in Table 7. Since appropriate S doping can improve the dielectric properties of the dielectric film, ZrSO X The on / off ratio of ln2O3 TFT devices increased from 1.96×10 4 (0at%) increased to 1.29×10 7 (10at%), so that the switching ratio of the TFT device reaches a level that can be used in practical applications. Fig.18 The output curve (b) in Figure 1 shows obvious local current saturation pinch-off in all devices, which is a typical feature of n-type channel devices. The saturation output current value of the device gradually decreases with the increase of S doping. This is related to the capacitance value of the dielectric film. A larger unit capacitance area can induce a larger concentration of carriers, which increases its saturation output current.
[0155] As the doping concentration increases, the capacitance values of the series films are 488, 343, 265, 287 and 304 nF / cm 2 . The capacitance value is obtained at 2V bias and 20Hz frequency. Here, the mobility of the device is calculated using the above capacitance value and is statistically shown in Table 7. The results show that appropriate S doping can improve the mobility of the corresponding device. Obviously, the improvement of the dielectric properties of the dielectric film will improve the carrier transmission efficiency and reduce the capture of carriers by traps, which is specifically manifested in the improvement of mobility. According to the interface state density (D it ) formula and subthreshold swing (SS) formula to calculate the numerical values of the series are shown in Table 7. Among them, the TFT corresponding to the dielectric film with S doping content of 10at% has the smallest SS (0.14) and D it (2.36×1012 ) value. Therefore, appropriate S doping can also improve the X Electrical properties of TFT devices with dielectric films.
[0156] Table 7 In2O3 / ZrSO based on different S doping amounts X TFT device performance parameter table
[0157]
[0158] like Fig.19 Series MSO shown X The AFM images of the surface morphology of the thin films (M=Ga, Sc, Ho, Sm) have a uniform scanning area of 2×2μm. From the scanning images, we can see that the surface of the prepared Sc2O3, Ho2O3, and Sm2O3 thin films is very bad before doping. The AFM images of the Sc2O3, Ho2O3, and Sm2O3 thin films show uneven solute dispersion and uneven films. In addition, their corresponding root mean square roughness (RMS) is 5.96, 10.6, and 12.86nm, respectively, which will make it difficult to use them as dielectric layers for TFT devices with good performance. ScSO doped with 10at% S X 、HoSO X 、SmSO X The film becomes obviously smoother, and the corresponding RMS are 1.80, 1.74, and 6.89 nm, respectively.
[0159] And through XRR test analysis, it is confirmed that the mass density of all dielectric films has been improved to varying degrees after doping with S. These phenomena well show that sulfate ions eliminate hydroxyl groups, thereby connecting the metal oxygen skeleton and making the film higher in quality.
[0160] At the same time, compared with the undoped dielectric film, 10at% GaSO X ScSO X 、HoSO X 、SmSO X The unit breakdown electric field strength of the films increased by 186.7%, 60.5%, 790%, and 490%, respectively. Appropriate S doping has a significant improvement on all the films in this series compared to undoped ones.
[0161] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing an S-doped high-K oxide dielectric film, characterized in that: Includes steps: Dissolving nitrate in water and stirring to obtain a nitrate solution; adding a sulfuric acid aqueous solution to the nitrate solution to obtain a precursor solution; Providing a substrate, and cleaning, drying, and plasma treating the substrate; Applying the precursor solution on the surface of the plasma-treated substrate and performing a pre-annealing treatment; Finally, a final annealing treatment is performed to obtain an S-doped high-K oxide dielectric film; The concentration of the precursor solution is 1.0-2.0 mol / L; the molar percentage of S element in the precursor solution to the sum of S and metal ions is 0 <a≤24at%。 2. The method for preparing an S-doped high-K oxide dielectric film according to claim 1, characterized in that: The nitrate is selected from one of AlN3O9·9H2O, N2O7Zr·xH2O, Ga(NO3)3·xH2O, N3O9Sc·xH2O, N3O9Ho·xH2O, and N3O9Sm·6H2O.
3. The method for preparing the S-doped high-K oxide dielectric film according to claim 1, characterized in that: The mass fraction of the aqueous sulfuric acid solution is greater than or equal to 70%, and the purity of the aqueous sulfuric acid solution is 98%.
4. The method for preparing the S-doped high-K oxide dielectric film according to claim 1, characterized in that: The steps of cleaning, drying and plasma treating the substrate include: The substrate is sequentially soaked in acetone, anhydrous ethanol and ultrapure water and ultrasonically cleaned for 8-12 minutes respectively; after cleaning, the substrate is blown dry with nitrogen and then placed in a plasma cleaning machine for plasma treatment in an oxygen atmosphere for 8-12 minutes.
5. The method for preparing the S-doped high-K oxide dielectric film according to claim 1, characterized in that: The coating method is spin coating; the rotation speed of the spin coating is 5000 rpm / s, and the spin coating time is 28-32s.
6. The method for preparing an S-doped high-K oxide dielectric film according to claim 1, characterized in that: The pre-annealing treatment is carried out at a temperature of 140-160° C. for 4-6 minutes; and the final annealing treatment is carried out at a temperature of 250-400° C. for 0.8-1.2 hours.
7. An S-doped high-K oxide dielectric film, characterized in that: The film is prepared by the method for preparing an S-doped high-K oxide dielectric film as described in any one of claims 1 to 6.
8. An application of the S-doped high-K oxide dielectric film as claimed in claim 7, characterized in that: The S-doped high-K oxide dielectric film is used as a dielectric layer of a thin film transistor.
9. The use of the S-doped high-K oxide dielectric film according to claim 8, characterized in that: The method for preparing the thin film transistor comprises the steps of: Dissolving indium nitrate powder in water and stirring to prepare an In2O3 precursor solution; After plasma cleaning the S-doped high-K oxide dielectric film, it is purged with nitrogen; coating the In2O3 precursor solution on the surface of the S-doped high-K oxide dielectric film after the nitrogen is purged, and performing annealing treatment to obtain an In2O3 active layer on one side of the S-doped high-K oxide dielectric film; Two spaced metal electrodes are deposited on the side of the In2O3 active layer away from the S-doped high-K oxide dielectric film to obtain the thin film transistor.
Citation Information
Patent Citations
Ion-doped thin film transistor and preparation method thereof
CN113517351A